Pemberdayaan Usaha Mikro, Kecil, dan Menengah (UMKM) melalui Implementasi Customer Lifetime Value (CLV): Sebuah Kegiatan Pengabdian Masyarakat di Kembangan Selatan, Indonesia - Kwarto, Febrian; Minanari, Minanari; Suprapto, Suprapto (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a major contribution to the national economy, but still face challenges in retaining customers in a sustainable manner. This research aims to implement the Customer Lifetime Value (CLV) approach to improve customer loyalty and business sustainability of MSMEs in Kembangan Selatan Urban Village, West Jakarta. The activity methods include training, digital finance assistance, data-based marketing strategies, and practical application of CLV. The program results show an increase in MSME actors' understanding of financial management and customer retention strategies. CLV training and mentoring encourage efficient resource allocation and significantly improve MSME competitiveness. This activity is also a direct learning medium for students and strengthens the role of universities in supporting the local economy.